'... speak that I may see thee': Bushmen, Bleek, language and race in South Africa - Voss, Tony (Kronos: Southern African Histories, 2017)
In historiography and folklore the Bushmen are South Africa 's autochthonous founders, and the Bleek archive is a key document in the country's ongoing attempts to forge an identity. Representing Bushmen offers a critique of this enterprise, but the central argument of Shane Moran's book is that hierarchical ideas of language and its history have been central to the genesis of racial attitudes in South Africa. Bleek was a linguist before he was an ethnographer and Moran gives a careful account o fBleek's On the Origin of Language and of the global context ofBleek's scholarship. Invoking the broadest humane perspective, requiring the closest attention to textual detail and facing up to the evasions and disappointments of early twentieth-century South Africa, Moran' s book concludes with a recognition that we have room for action and grounds